2020
DOI: 10.1049/iet-sen.2019.0262
|View full text |Cite
|
Sign up to set email alerts
|

Requirements knowledge acquisition from online user forums

Abstract: Online discussion forums can be used for reflecting on the overall user experience of a system. If a user forum is well-structured, it can be a valuable source of requirements-related information, which can potentially be accommodated in the requirements engineering process to enhance the current and future software. However, presently, there are limited approaches for extracting such requirements-related information from the relevant community forums. To fill this gap, this study proposes an automated approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In the future, we aim to conduct exploratory research studies on the trusted facet ensured by the software vendors and developers through the end‐user feedback collected from these social media platforms. Another future direction is to identify critical stakeholders 41 in the Google Play Store and prioritize or group 42,43 them based on their severe deceptive review contributions to provide remedies in either blocking, limiting, or restricting them to enhance end‐user trust in the software applications 20 . Another possible future direction is to employ the extended proposed approach in the Internet of Medical Things (IoMTs) to identify the malware that seriously threatens medical software assets, such as abusing critical information, sensitive patient data, and so forth 44–48 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the future, we aim to conduct exploratory research studies on the trusted facet ensured by the software vendors and developers through the end‐user feedback collected from these social media platforms. Another future direction is to identify critical stakeholders 41 in the Google Play Store and prioritize or group 42,43 them based on their severe deceptive review contributions to provide remedies in either blocking, limiting, or restricting them to enhance end‐user trust in the software applications 20 . Another possible future direction is to employ the extended proposed approach in the Internet of Medical Things (IoMTs) to identify the malware that seriously threatens medical software assets, such as abusing critical information, sensitive patient data, and so forth 44–48 .…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have revealed that feedback analytics is pivotal in software and requirements engineering to make essential decisions. 2,20 Recently, Dhinakaran et al 21 used active and machine-learning approaches to identify new features from social media platforms. Maalej and Nabil 22 and Khan et al 9,23,24 utilized ML and DL classifiers to capture and identify bugs or issues in end-user feedback.…”
Section: Mining End-user Feedback For Requirements Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Massive usergenerated content has extremely high mining and utilization value. Compared with service log data, user comment data are easier to obtain on web pages where the data are disclosed (Khan et al, 2020). User comment data usually include numbers, review text, and images (Hossin et al, 2019).…”
Section: Data Collectionmentioning
confidence: 99%
“…• Ali et al [66] and Han et al [75] used user comments on Facebook and Weibo, respectively. Seven out of 11 studies that used microdata performed sentiment analysis of tweets [64-66, 68, 69, 72, 73] Online discussion/forum Eight studies (12%) elicited requirements from different online discussion forums: online forum posts from the feature tracker of the Password Safe project on SourceForge [76], questions and answers on Stack Overflow [77], and feature requests from open-source forums of SugarCRM, SecondLife, and an Amazonlike portal specifically developed for students [78], OpenOffice online discussion forum [79], the Reddit forum [80][81][82], and the VLC media player and Firefox web browser forums [83]…”
Section: Microblogsmentioning
confidence: 99%